Lubrication of synovial membrane. Issue 1 (February 1976) - Cooke, A F; Dowson, D; Wright, V
Abstract : (1) An apparatus has been constructed to measure the coefficient of friction of synovial membrane against a glass slider. (2) Provision was made to vary the load on the specimens. (3) The coefficient of friction varied from 0-006 to 0-07. (4) A presentation similar to that used in the Sommerfeld analysis of journal bearings indicated that in these experiments synovial membrane was lubricated in the hydrodynamic regimen.